The Role of CCUS in North America Energy System Decarbonization - Victor, Nadejda; Balash, Peter; Nichols, Christopher (Journal of Strategic Innovation and Sustainability, 2019)
One of the key energy technologies that can significantly reduce carbon dioxide (CO2) emissions across industrial processes and power generation is carbon capture, utilization, and storage (CCUS). We explore different scenarios of North America long-term energy system development with respect to CCUS technologies and, particularly, CO2-enhanced oil recovery (EOR).